Dedovanje in pravo EU - Žnidaršič Skubic, Viktorija (Pravni letopis, 2008)
In this article the author deals with the problem of Succession Law from the EU perspective. She emphasizes that for the time being we can not talk about European Private International Law on Succession. We also can not, at least in a very near future, count on harmonization of substantial Succession Law. The latter is, by the opinion of majority of authors and also by the opinion of the author of this article, practically unfeasible or impossible, the question is also if it is really desirable. On certain areas, among which is also the area of inheritance, the historical legal development in different countries brought certain specifics that should be considered and respected and not changed or adapted to others. Doubtlessly we should welcome the project of EU which is about to bring a great relief to the difficulties in the area of so called international inheritance. As the main mean for the achievement of a set goal the process of harmonization and unification of the rules on Private International Law on the field of succession will be used.
Keywords: dedno pravo; dedovanje; European Union; Evropska unija; Trusts and estates